Combination Test of Organic Fertilizer with Inorganic and Use of Insecticide on Sweet Corn (Zea mays saccharate Sturt.) Production - ‎ , Hapsoh; ‎ , Wawan; Salbiah, Desita; Yulia, Arnis En; Dini, Isna Rahma; Fadilah, Widya Nur (KnE Social Sciences, 2024)
The continuous and excessive use of inorganic materials such as fertilizers and pesticides in maize cultivation can cause land degradation. Therefore, to restore the quality of degraded land, it is necessary to add organic matter to the soil. This study aims to determine the growth and production of sweet corn (Zea mays saccharata Sturt) by reducing the use of inorganic fertilizers and chemical insecticides. This research was carried out in Langsat Permai Village, Bunga Raya District, Siak Sri Indrapura Regency, Riau Province from July to October 2020, using a completely randomized design (CRD) factorial, consisting of two factors. The first factor is fertilization consisting of four levels, namely 100% inorganic fertilizer + 16 ton.ha−1 organic fertilizer, 75% inorganic fertilizer + 20 ton.ha−1 organic fertilizer, 50% inorganic fertilizer + 24 ton.ha−1 organic fertilizer, and 25% inorganic fertilizer + organic fertilizer 28 ton.ha−1. The second factor is the type of insecticide, which consists of three levels, namely chemical insecticides, semivegetable insecticides, biological insecticides. The results showed that the use of 25% inorganic fertilizer with 25 ton.ha-1 organic fertilizer and the use of semi-vegetable and biological insecticides showed better production in the parameters of weight per ear with husk, weight per ear without husk, and weight of cob with husk per plot. Therefore, organic fertilizers and bioinsecticides can be used to support environmentally friendly maize farming. Keywords: insecticide, plant growth, production